Development Of Conflict Resolution Education Model In Banyuwangi District Senior High School - Suharso, Pudjo; Zulianto, Mukhamad; Sumardi, Sumardi; Sedyati, Retna Ngesti; Yushardi, Yushardi (Universitas Pendidikan Indonesia, 2023)
The Tumpangpitu mine conflict that occurred in Pancer Pesanggaran village in Banyuwangi not only involved communities with mining pros and cons but also involved students in high schools around mining. The horizontal conflict that was manifested by various protests was followed by the children of parents involved in the competition in the Pesanggaran District. So that the conflict does not spread and impact schools, this study aims to analyze the development model of conflict resolution education in high schools in Banyuwangi to minimize conflicts. The research method uses a mixed, quantitative, and qualitative approach—data collection with questionnaires for students and in-depth interviews with high school teachers in Banyuwangi. As a result, students get into conflict because they jump on the bandwagon. The development model of conflict resolution education is more towards integrating conflict resolution education with other subjects. From the discussion through the focus group discussion, the teachers revealed that this integration model is considered the most suitable because, with its issue, the burden on teachers and students is already very high.